Targeting glycolysis in Th2 cells by pterostilbene attenuates clinical severities in an asthmatic mouse model and IL‐4 production in peripheral blood from asthmatic patients - Liu, Chuan‐Teng; Song, Ying‐Chyi; Wu, Tsai‐Chen; Shiung, Ko‐Chieh; Chen, I‐Hsuan; Chang, Tung‐Ti; Liang, Shinn‐Jye; Yen, Hung‐Rong (Immunology, 2022)
Asthma, a major non‐communicable disease, affects both adults and children and is associated with high morbidity compared with other chronic diseases. The glycolysis‐associated activation of type 2 helper T (Th2) cells is the critical immunopathological mechanism involved in asthma deterioration. Long‐term use of steroids as a medical treatment for asthma induces side effects and resistance. Pterostilbene (PS), a stilbenoid compound found in blueberry and vines, exhibits antihyperglycemic and anti‐inflammatory properties. Thus, we hypothesized that the modulation of T cell immunity by PS may be an applicable intervention to treat asthma. Airway hyperresponsiveness, interleukin (IL)‐4 and IL‐13 levels, IgE, IgG, pulmonary infiltrated monocytes and eosinophils, and mucosubstances were measured in house dust mite (HDM)‐induced asthmatic mice under PS treatment. Bioenergetic metabolism, PI3K‐mTOR signalling, GATA3 expression and histone acetylation in PS‐treated Th2 cells were investigated. PS improved HDM‐induced pulmonary allergic airway inflammation by inhibiting Th2 cell and eosinophil accumulation in HDM asthmatic mice both in the preventive and therapeutic models. Targeting glycolysis resulted in IL‐4 inhibition via the downregulation of mTOR, GATA3 and histone acetylation in PS‐treated Th2 cells. Glucose supplementation reversed the inhibitory effect of PS on Th2 cells in vitro. Adoptive transfer with glucose‐treated Th2 cells enhanced Th2 activation and eosinophilic accumulation in PS‐treated asthmatic mice. Furthermore, PS significantly inhibited IL‐4 production of CD4+ T cells from the peripheral blood mononuclear cells of patients with asthma. PS attenuates HDM‐induced asthma via the inhibition of the Glut1/mTOR/GATA3 axis in Th2 cells, which supports the potential pharmaceutical application of PS treatment for asthma. The inhibition of glycolysis by blocking glucose transportation is involved in pterostilbene's anti‐Th2 and anti‐eosinophil immune responses, which relieve bronchoconstriction. The downregulation of the mTOR‐GATA3 axis contributed to epigenetic changes through histone deacetylation in pterostilbene‐treated Th2 cells and ultimately led to a decrease in IL‐4 and IL‐13.